Improving Arabic Speaking Skills through the Muhadathah Method among Eighth-Grade Students of MTs Al Irsyad Tengaran - Agus Walid Khamdani; Joko Subando (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to improve Arabic speaking skills through the implementation of the Muhadathah method among eighth-grade students of MTs Al Irsyad Tengaran. The research employed a Classroom Action Research (CAR) approach, focusing on addressing students’ difficulties in speaking Arabic, particularly in terms of pronunciation, vocabulary mastery, and fluency. The Muhadathah method was selected as an instructional strategy to encourage active verbal interaction and to create a communicative learning environment in Arabic language instruction. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research sample comprised 30 eighth-grade students. Data were collected through speaking performance tests, classroom observations, and documentation. The collected data were analyzed using descriptive quantitative and qualitative methods to measure improvements in students’ speaking skills and to evaluate the effectiveness of the instructional process. The findings reveal a substantial improvement in students’ Arabic speaking skills following the implementation of the Muhadathah method. The percentage of students achieving the minimum mastery criteria increased from 40% in the pre-cycle, to 66.7% in Cycle I, and further to 86.7% in Cycle II. These results indicate that the Muhadathah method is effective in enhancing students’ Arabic speaking skills and fostering greater participation and confidence in classroom communication